Legitimacy and violence in information and journalism - Pacheco Benites, Alberto (2014)
This text reflects on the current situation of information and the performance of journalism, since they approach to the (re)presentation of the phenomenon of violence and its legitimation in the media. Therefore, three analysis perspectives are set. First, the current context of information practices and the dimensions of the value of information, journalismand legitimation strategies are described. Secondly, the relationships derived from journalistic coverage of violence and its implications (linked to the legitimacy of the phenomenonon a discursive level) are presented. Finally, to conclude two so-called “vices” of  the operation of the information institution, deeply related to the phenomenadescribed above are reviewed.